POTENSI PELANGGARAN DESAIN INDUSTRI TERKAIT IMPLEMENTASI PERJANJIAN LISENSI KERAHASIAAN DALAM WARALABA - Siahaan, Shinta Aulia; i, Urbanisasi (Peneliti.net, 2023)
The increasing development of the economic and industrial sectors requires legal protection for this matter. Industrial design being the face of a franchise is something that can't be separated. To guarantee the existence of a franchise, an agreement is needed that contains a confidentiality license to protect the quality and the absence of plagiarism or counterfeiting. With a confidentiality clause, it can make the design secret of a franchise known only to the parties. However, in practice, violations of this clause often occur. The basic rules used as a reference in this writing are Law Number 31 of 2000 concerning Industrial Design and Government Regulation Number 42 of 2007.